Framework for Tacit Knowledge Loss Mitigation in South African Public Sector Enterprises - Malefetjane Phineas Phaladi (Administrative Sciences)
In order to mitigate the risks of losing key personnel and their innate tacit knowledge resources, this paper explored a framework for reducing knowledge loss in South African public sector enterprises (PSEs) through the integration of knowledge management (KM) and human resource management (HRM) strategies. The study used a quantitative research design, administering survey questionnaires to 585 randomly selected employees in three South African PSEs. The survey yielded a 25% response rate and was analysed using Statistical Analysis Software, resulting in a Cronbach alpha of 0.94. The findings of the exploratory factor analysis showed that a framework for reducing knowledge loss can be developed by integrating HRM practices and focusing on seven factors: knowledge loss recognition, knowledge management practices, human resource training, organisational culture, recruitment practices, employee retention, and organisational barriers. Three important components constitute the developed framework for knowledge loss minimization. Tacit knowledge loss was recognised as a critical strategic issue based on the results of the chi-square test for independence and logistic regression. This realisation, along with control and intervention variables, created the three main components of the framework. This paper explored the Knowledge Loss Reduction framework, focusing on South African PSEs as a case, to help organisations address the complex tacit knowledge loss prevalent in public and commercial firms worldwide. It contributes to the knowledge-based view, focusing on knowledge-absorptive and -retentive capacities and praxis in knowledge (risk) management and human resource management.